Między historią, tradycją a narracją. Powstanie Muzeum Bitwy Legnickiej w Legnickim Polu na tle pramuzealnych i muzealnych upamiętnień bitwy z 1241 r. - Byś, Konrad (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2021)
The paper concerns the circumstances of the establishment of the Museum of the Battle of Legnica in the village of Legnickie Pole in Lower Silesia. The most important figures who contributed to organizing the the museum and its subsequent functioning are discussed. Furthermore, the article is an attempt to depict the museum in a broader context of the tradition of commemorating the Battle of Legnica in non-museum forms – such tradition was rarely taken into consideration so far.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne